PERANCANGAN SISTEM INFORMASI PEMESANAN JASA JAHIT PADA MASA PANDEMI DIKOTA MEDAN MENGGUNAKAN METODE COLLABORATIVE FILTERING - Dina Ulfiani; Ahmad Zakir; Boni Oktaviana Sembiring (METHOMIKA: Jurnal Manajemen Informatika & Komputerisasi Akuntansi, 2021)
Pandemics covid-19 had an impact a slowing economy are one of them is UMKM sector. Residents who work as a seamstress experienced dependence of the production of his income had also won three others. Because of the movement of people so that the decline in economic transactions during the social distancing has experienced a fall in. Therefore, it takes a system to do reservations tailor services without have to do a lot of movement in the time of 33 countries. Building these systems uses the method collaborative filtering where this method used to know a tailor who recommended data they would purchase and the number of ratting any reservations. System that built using language php programming and a database MySQL format and use framework Codeigniter 3. With the reservations system sewing services could help residents of the city of Medan to booking for tailor services in the pandemic and by the presence of collaborative filtering can ease the reservation to know the tailor who recommended if do not know to which tailor order. Keywords : Booking, Tailor Services, Collaborative Filtering.